Relationship among different performance tests to estimate maximal aerobic swimming speed - Matsunami, M.; Taguchi, M.; Taimura, A.; Suga, M.; Taba, S. (Medicine & Science in Sports & Exercise, 1999)
The T-30 and T-2000 swimming performance tests measure maximal lactate steady state but require great amounts of time. This study attempted to contrive a test to elicit endurance capacity in the shortest time possible. Trained male swimmers (N = 7) completed six performance tests: T-30, T-2000, T-1500, T-10, T-600, and a critical speed test. The velocity that produced OBLA was determined by a lactate step-test. The highest mean swimming velocity was in the T-600 swim and the lowest in the T-2000. All tests were significantly related to OBLA velocity. T-30 and T-2000 were significantly lower in velocity when compared to the other four tests and OBLA velocity. T-10 yielded the closest relationship to OBLA velocity. Implication: A T-10 test is a practical test to determine maximal aerobic swimming velocity.